Fiscal Decentralization and Financial Condition: The Effects of Revenue and Expenditure Decentralization on State Financial Health. (June 2018) - Singla, Akheil; Stone, Samuel B.
Although there are strong theoretical arguments about both the benefits and costs of decentralization in the federalism literature, there is little on how second-order fiscal decentralization effects the financial health of state governments. This study examines this question and adds to the understanding of state-and-local fiscal relations. Using financial indicators that measure several dimensions of financial condition, the research estimates the effect of revenue and expenditure decentralization on state fiscal health. It finds that while state financial condition is unaffected by revenue decentralization, there is a curvilinear relationship between expenditure decentralization and long-term state financial condition.